Strengthening Management of Local Human Resources to Create A Sustainable Green Tourism Destination at Lantan - Zahrah Zahrah; Makiah Makiah; Bagas Anggara; Laela Purnama; Rafles Rafles (Jurnal Masyarakat Madani Indonesia, 2025)
There are still various challenges to develop sustainable tourism villages especially on human resources such as limited technical guiding skills in conveying information about local tourism attractions based on the green economy, limited effective interaction, minimal understanding of local communities regarding digital marketing strategies and the lack of adequate technology to produce more efficient production in terms of time and costs so they have other alternatives to generate income. This community service aims to improve the local human resource capacity in Lantan Village, Central Lombok, to develop a sustainable green tourism through doing a guide and tourism vocabulary training, strengthening the branding of coffee as the village's flagship product, mentoring in developing partnership proposals, and empowering in managing coffee product as competitive advantages. The methods included interactive lectures, conversation simulations, small group discussions, pronunciation drills, pre and post-tests. The results of the activity showed a significant increase in participants' understanding of how to guide tours, build branding, improve basic English communication skills, and coffee product management particularly in the process of peeling coffee beans from the skin and faster in roasting coffee. This activity significantly contributed to increasing Lantan Village's readiness to develop itself as a sustainable green tourism destination.